Viewing Aggregation-Induced Emission of Metal Nanoclusters from Design Strategies to Applications - Tingting Li; Haifeng Zhu; Zhennan Wu (Nanomaterials, 2023)
Aggregation-induced emission (AIE)-type metal nanoclusters (NCs) represent an innovative type of luminescent metal NCs whose aggregates exhibit superior performance over that of individuals, attracting wide attention over the past decade. Here, we give a concise overview of the progress made in this area, from design strategies to applications. The representative design strategies, including solvent-induction, cation-induction, crystallization-induction, pH-induction, ligand inheritance, surface constraint, and minerals- and MOF-confinement, are first discussed. We then present the typical practical applications of AIE-type metal NCs in the various sectors of bioimaging, biological diagnosis and therapy (e.g., antibacterial agents, cancer radiotherapy), light-emitting diodes (LEDs), detection assays, and circularly polarized luminescence (CPL). To this end, we present our viewpoints on the promises and challenges of AIE-type metal NCs, which may shed light on the design of highly luminescent metal NCs, stimulating new vitality and serving as a continuous boom for the metal NC community in the future.